Challenges impacting student learning in the International Baccalaureate Middle Years Programme. (December 2020) - Dickson, Anisah; Perry, Laura B; Ledger, Susan
While the International Baccalaureate's Middle Years Programme (MYP) is growing in popularity in Australia and across the globe, few studies have examined the benefits and challenges of this IB programme for supporting student learning. Using a qualitative case study design of three Australian schools that formerly offered the MYP, we investigated teacher and school leader perceptions of the MYP for promoting student learning. Perceived benefits included high achievement and skill development through the MYP's emphasis on inquiry-based learning and real-world relevance; criterion-referenced assessments; and a healthy balance between core and elective learning areas. Challenges for students stemmed primarily from operational difficulties and possible systems-level constraints impacting teachers, including integration of the Australian Curriculum with the MYP; ability to meet the MYP's demands; confusion about MYP terminology and grading systems; and understanding interdisciplinary units. The findings suggest that MYP Coordinators and school leaders play a critical role in ensuring that schools realise the benefits of the MYP for student learning by providing systems-level support to optimise its benefits.